(untitled) (Ustozlar uchun, 2024)
Abstract: Language as the Mirror of the Nation explores the importance of language in relation to a nation and its culture, history and identity. Language is an important tool that reflects the identity, customs and values ​​of each nation. This article analyzes the role of language as a mirror of the nation, its role in preserving cultural heritage, its importance in strengthening national identity, and its role in educational processes. Also, globalization processes and the need to preserve the language in modern socio-economic conditions are also considered. The article emphasizes that language is not only a means of communication, but also an important factor for the psyche and future of a nation. By preserving language, we are able to pass on our culture, history and identity to future generations.